Developing E-Government Maturity Framework Based on COBIT 5 and Implementing in City Level: Case Study Depok City and South Tangerang City - Fikri Akbarsyah Anza; Dana Indra Sensuse; Arief Ramadhan (IAES Indonesia Section, 2017)
The use of E-Government in achieving good governance has been done by government to serve citizen nowadays. However, not all local government were able to implement it. PeGI that has been used as a benchmark to check government’s readiness rate in implementing E-Government can’t describe all process that need to be assessed in developing local E-Government. Moreover, the emergence of social problems, such as organizational culture and human resource management which inhibits maturation of local E-Government. Therefore, it needs one general maturity framework which capable to guide local government to develop their own E- Government and able to address social problems that arise. This study is the incorporation of previous research results using meta-synthesis method combine with best practice, primary in COBIT 5 that has been adjusted to address a factor of social problems. The design framework begins with identifying the business principle of local government, stakeholders, concerns, requirements, and obstacles; thus, produced a model of maturity framework that has six types stages, eight types dimensions, four types main categories and 69 types sub-category of assessment processes. In the end, after the framework was tested and evaluated, we can conclude this framework already comply with PeGI’s result. From local government who had the best PeGI’s result, they had main problem in social issues and in documenting process. For local government with very low PeGI’s result, they had common constraints related to IT (low understanding of IT governance and IT management, lack of infrastructure, human resources, and understanding how to use IT Master Plan).